Catalogue of type materials of springtails (Hexapoda, Collembola) in the Canadian National Collection of Insects, Arachnids & Nematodes - Stebaeva, Sophya; Lonsdale, Owen; Babenko, Anatoly (Zootaxa, 2016)
The catalogue assembles and updates all data concerning the type material of Collembola kept in the Canadian National Collection of Insects, Arachnids & Nematodes in Ottawa (CNC). Information is provided for type material of 69 species. Included are holotypes of 31 species (together with 5 ones from Cretaceous amber), syntypes of 26 species (four of them are presently considered to be junior synonyms) and paratypes of 32 species (one of which is considered a junior synonym). Essential label data, references to original descriptions, and modern status including synonyms are given.